Physical properties of three soils in southern Nigeria - Mbagwu, J.; Lal, R.; Scott, T.W. (1983)
To determine their physical characteristics, we studied two Alfisols and an Ultisol in southern Nigeria. The soils are formed over different parent materials. Moisture retained at saturation, 0.1, and 0.3 bar suctions was significantly correlated with available water-holding capacities. The regression models depicting the relationships between moisture equilibria and the sand, clay, and organic carbon contents had high and significant coefficients of determination and indicate that variations in soil particle size fractions and organic carbon contents accounted for over 70 percent of the variability in moisture retanined at different suctions. Significant correlation exists between organic carbon and macroporosity (r = 0.63*]) and saturated hydraulic conductivity (r = 0.88**]). Soil bulk density is negatively correlated with the organic matter content. Similarly, the percentage of clay is negatively correlated with macroporosity (r = —0.75**]) and with saturated hydraulic conductivity (r = —0.76**]), and the percentage of sand is positively correlated with these properties, with r values of 0.62**] and 0.67**], respectively.